Teks Geguritan Dharmakerti (Kajian Nilai-Nilai Pendidikan Karakter) - Pradnyana Anggara, I Putu; Linggih, I Nyoman; Saputra, I Made Dian (UHN IGB Sugriwa Denpasar, 2024)
The Geguritan Dharmakerti text is one of the classical Balinese literary works rich in spiritual moral values useful in life. This is appropriate to be observed in order to preserve and develop the nation's culture, especially the local culture. Geguritan literature was created in the form of a diverse collection of pups or quarries complete with their respective rules. he issues to be discussed include: (1) How is the structure of the text of Geguritan Dharmakerti (2) What the text of Geguritan Dharmakerti functions in character education (3) The educational values of the characters are contained in the Geguritan Dharmakerti text. This study aims to find out (1) The structure of the text of Geguritan Dharmakerti (2) The function of Geguritan Dharmakerti text in character education (3) The educational values of the character are what is in Geguritan Dharmakerti text. The theories used to solve problems in research are structural theory of Teeuw, function theory of Robson and character education theory of Thomas Lickona. The subjects of this study were those who were trusted as informants. Data collection methods are library studies, interviews and documentation. The collected data are analyzed using hermeneutical data analysis methods that are interpreted. Research results show (1) The structure in the text of Geguritan Dharmakerti is divided into a formal structure consisting of stanza, pupuh, skema wilangan wanda, character from the pupuh, and narrative structure consisting of the background, figure, plot and themes (2) Geguritan Dharmakerti text function in character education, i.e. function is activated (educational), morality, aesthetic and recreational functions (3) The educational values of the characters found in the Geguritan Dharmakerti text are the values of the character's faith and noble character, global independence and cooperation.